ENTERPRISE-WIDE RISK MANAGEMENT - Dougherty, David (Assurances)

(untitled) (HEC Montréal, 2000)
The purpose of this paper is to provide an assessment of the impact of Enterprise-wide Risk Management (ERM) on the trading activities of financial institutions, with an emphasis on derivatives. This paper is divided into three parts. The first part looks at the evolution of ERM in terms of its impact on the culture of the organization, risk coverage, measurement methodologies, technology and performance measurement. The second part looks at the application of ERM as it relates to individual risk types such as market, credit, and business risks. The paper concludes with an overview of the key factors that are critical to the success of an ERM program.